2017
DOI: 10.17017/j.fish.49
|View full text |Cite
|
Sign up to set email alerts
|

Fish catch composition of selected small scale fishing gears used in the Bonny River, Rivers State, Nigeria

Abstract: Fish catch composition of some selected small scale fishing gears (gill net, cast net, beach seine and long line) were investigated in Bonny River, Rivers State, Nigeria from August 2014 to January 2015. A total number of 25 fish species from 18 families were recorded during the study. The Mugilidae with only one species constituted the dominant family while Cichlidae, Lutjanidae, Clupeidae, had three species and Scianidae had two species of fish caught and the remaining families had one species each. Mugil ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Competition among fishing methods, as evidenced by the overlap in species composition across these methods, is a common characteristic in small-scale, multi-gear, and multi-species fisheries. For example, a study of the catch composition of four fishing gears (cast net, beach seine, gillnet, and longline) in the Bonny River, Nigeria, showed competition over some dominant species in the family Mugilidae (mullet) [62]. In addition, the study by Humphries et al [63] in West Lombok, Indonesia also showed that handlines and spearguns competed in targeting some key reef fish species such as the siganids Acanthurus mata and Naso caeruleacauda and the scarid Scarus goban.…”
Section: Variation Of Catches Among Fishing Methodsmentioning
confidence: 99%
“…Competition among fishing methods, as evidenced by the overlap in species composition across these methods, is a common characteristic in small-scale, multi-gear, and multi-species fisheries. For example, a study of the catch composition of four fishing gears (cast net, beach seine, gillnet, and longline) in the Bonny River, Nigeria, showed competition over some dominant species in the family Mugilidae (mullet) [62]. In addition, the study by Humphries et al [63] in West Lombok, Indonesia also showed that handlines and spearguns competed in targeting some key reef fish species such as the siganids Acanthurus mata and Naso caeruleacauda and the scarid Scarus goban.…”
Section: Variation Of Catches Among Fishing Methodsmentioning
confidence: 99%